Ceramics with adjustable dielectric properties based on the system SrO – TiO₂ – SiO₂ - Lisachuk, Georgy; Kryvobok, Ruslan; Pitak, Yaroslav; Lapuzina, O.; Gusarova, Irina; Lisachuk, Lidiya; Grebenyuk, Andrey (My University, 2018)
This work presents the results of optimization of the compositions area of radio-absorbing ceramic. As a result of laboratory samples test, dependences "composition – property" was obtained, the choice of the most technologically advanced composition area and sintering temperature for manufacturing the radio-absorbing ceramic was substantiated. The optimal composition of the Sr- titanate ceramics is characterized by the following properties: water absorption (W = 1,3 %), dielectric permeability (ε = 115), density (ρ =4,35·10³ kg/m³).
Keywords: radio-transparent materials; radio-absorbing materials; strontium titanate; water absorption